Experimental study of high temperature on the shear properties of early-age concrete - Li, Meilin; Gan, Fei (Frontiers in Materials, 2023)
Fire accidents happen randomly which may occur in the construction of concrete buildings. In this study, the effects of high temperature and curing ages on shear properties of early-age concrete were experimentally studied. The pore structure of early-age concrete before heating, after heating, and re-curing after heating were examined through NMR (nuclear magnetic resonance) and SEM (scanning electron microscope) tests. Experimental results reveal that high temperature treatment of earlyage concrete multiplies the number of pores but has little influence on the change of pore size distribution, while the re-curing treatment reduces pore size but has little influence on the change of pore numbers. Under the same exposed temperature, the shear strength of concretes before heating, after heating, and re-curing after heating increases gradually with curing ages. For concretes with certain curing ages, the shear strength increases first and then decreases with the exposed high temperature. While the cohesion and internal friction angle show a negative relationship with elevated temperature. The research can provide base data for buildings encountering fire accidents.